Electro-Hydrostatic Actuator (EHA) Position Tracking and Correction - Hu, Xiang (My University, 2015)
The Electro-Hydrostatic Actuator (EHA) is a self-contained and modular hydraulic actuation system using feedback control. EHAs are being increasingly used in engineering and industrial systems that require high precision and efficiency such as aircrafts (Airbus 380), off-highway hydraulic hybrids and construction machineries. In this research, mathematical models (linear and nonlinear) with different control strategies (that include PID, PID with feedforward compensation, and Sliding Mode Control (SMC)) are developed and experimentally applied to an EHA prototype. These methods are then compared to a new control strategy that is a combination of Interacting Multiple Model concept, Sliding Mode Control (IMM-SMC) and the Smooth Variable Structure Filter (SVSF). The IMM and the SMC strategies are also applied with the Kalman Filter (KF) for comparison. The above mentioned control strategies were implemented on an EHA prototype for position control under a range of fault conditions that were physically simulated. Both simulation and experimental results showed that the new IMM-SMC with SVSF outperformed all the other control strategies in terms of robustness and precision in trajectory tracking.
Keywords: EHA; Control